Recombinant protein expression in Acanthamoeba castellanii - Salunke, Pooja; Kondabagil, Kiran; Karpe, Yogesh A. (Frontiers in Bioengineering and Biotechnology, 2025)
The ongoing quest to improve protein production efficiency, quality, and versatility fuels the exploration of novel expression systems. In this research, we explored the potential of the axenically culturable Acanthamoeba as an alternative for producing recombinant eukaryotic proteins. We constructed plasmid vectors utilizing the TBP promoter to facilitate recombinant protein expression within this protozoan system. Our primary objectives were to develop an efficient transfection method and assess the capacity of Acanthamoeba castellanii for glycoprotein expression. Our initial efforts yielded successful expression of the firefly luciferase reporter gene, allowing us to optimize the transfection protocol. Subsequently, we compared the expression of the Chikungunya virus E2 protein across three systems: E. coli, Acanthamoeba, and mammalian cells. Interestingly, the E2 protein expressed in Acanthamoeba exhibited a molecular weight higher than bacterial cells but lower than mammalian cells, suggesting the possibility of glycosylation occurring in the protozoan system. These findings collectively suggest that protozoa, like A. castellanii, represent a promising avenue for developing low-cost and efficient eukaryotic expression systems.